Candidate transmission survival genome of Mycobacterium tuberculosis - Saurabh Mishra; Prabhat Ranjan Singh; Xiaoyi Hu; Landys Lopez-Quezada; Adrian Jinich; Robin Jahn; Luc Geurts; Naijian Shen; Michael A. DeJesus; Travis Hartman; Kyu Rhee; Matthew Zimmerman; et al. (Proceedings of the National Academy of Sciences, 2025)
Mycobacterium tuberculosis (Mtb), a leading cause of death from infection, completes its life cycle entirely in humans except for transmission through the air. To begin to understand how Mtb survives aerosolization, we mimicked liquid and atmospheric conditions experienced by Mtb before and after exhalation using a model aerosol fluid (MAF) based on the water-soluble, lipidic, and cellular constituents of necrotic tuberculosis lesions. MAF induced drug tolerance in Mtb, remodeled its transcriptome, and protected Mtb from dying in microdroplets desiccating in air. Yet survival was not passive: Mtb appeared to rely on hundreds of genes to survive conditions associated with transmission. Essential genes subserving proteostasis offered most protection. A large number of conventionally nonessential genes appeared to contribute as well, including genes encoding proteins that resemble antidesiccants. The candidate transmission survival genome of Mtb may offer opportunities to reduce transmission of tuberculosis.